HIV1‐viral protein R (Vpr) mutations: associated phenotypes and relevance for clinical pathologies. (6th June 2016) - Soares, Rui; Rocha, Graça; Meliço‐Silvestre, António; Gonçalves, Teresa
Summary: Over the last 30 years, research into HIV has advanced the knowledge of virus genetics and the development of efficient therapeutic strategies. HIV‐1 viral protein R (Vpr) is a specialized and multifunctional protein that plays important roles at multiple stages of the HIV‐1 viral life cycle. This protein interacts with a number of cellular and viral proteins and with multiple activities including nuclear transport of the pre‐integration complex (PIC) to the nucleus, transcriptional activation, cell cycle arrest at G2/M transition phase and induction of cell death via apoptosis. Specifically, Vpr has been shown to control many host cell functions through a variety of biological processes and by interaction with several cellular pathways. The different functions of Vpr may enhance viral replication and impair the immune system in HIV‐1 infected patients. Importantly, functional defects induced by mutations in the Vpr protein correlate with slow disease progression of HIV‐infected patients. Vpr is also associated with other concomitant pathologies developed by these patients, which may lead it to be considered as a potential novel therapeutic target. This review will focus on HIV‐1 Vpr, mainly on the importance of its structural mutations on the progression of HIV infection, associated phenotypes and relevance for clinical pathologies. Copyright © 2016 John Wiley & Sons, Ltd.